The Colours of Infinity The Beauty and Power of Fractals - Lesmoir-Gordon, Nigel; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
The groundbreaking documentary accompanying this book (visit extras.springer.com) is presented by Arthur C Clarke with music by David Gilmour of Pink Floyd. Introduced fifteen years ago, this brought the subject of fractals to the attention of the general public for the first time; since then it has been shown in over fifty countries around the world. Contributors to the film are joined by other leading experts in this latest edition of ‘The Colours of Infinity’, a comprehensive survey of fractal theory and practice. Incorporating an additional chapter on the money markets by the fractal master himself, Professor Benoit Mandelbrot, the documentary has also been re-mastered providing stunning new fractal animations. A must read for anyone with an interest in the ‘beauty and power of fractals’.
The Nature of Fractal Geometry -- Exploring the Fractal Universe -- A Geometry Able to Include Mountains and Clouds -- Fractal Transformations -- Fractal Limits: The Mandelbrot Set and the self-similar tilings of M. C. Escher -- Self-organization, Self-regulation, and Self-similarity on the Fractal Web -- Fractal Financial Fluctuations -- Filming The Colours of Infinity -- The Colours of Infinity-The Film Script.
Keywords: Mathematics; Geometry; Computational complexity; Popular Science in Mathematics; Geometry; Complexity